Peningkatan keterampilan guru IPA di Kabupaten OKU-Selatan melalui pendampingan pembuatan instrumen asesmen diagnostik - Dewi, Safira Permata; Santoso, Lucia Maria; Ermayanti, Ermayanti; Santri, Didi Jaya (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
The implementation of the Merdeka Curriculum emphasizes the execution of diagnostic assessments before the commencement of the learning process. This assessment aims to provide teachers with an understanding of students' initial capabilities, serving as a foundation for differentiated learning. This training is targeted at junior high school science teachers in South OKU Regency to enhance their skills in creating diagnostic assessment instruments. The method employed involves training 13 science teachers, conducted on September 3-4, 2023, encompassing material delivery, question-and-answer sessions, workshops, independent work, and product monitoring. The final product of this training is a diagnostic assessment instrument applicable in classroom learning processes. The product evaluation criteria include the selection of concepts, the appropriateness of answer choices to the questions, and the alignment of material with students' cognitive levels. The evaluation results indicate that participants have successfully created diagnostic assessment instruments aligned with textbook concepts. However, the development of alternative answers, both at the first and second levels, still requires further improvement. This challenge is attributed to the teachers' lack of practice in formulating effective answer alternatives.